Repositioning gender relations: exploring the auteur and nego-feminism theories in contemporary nollywood films (2020)
Gender stereotypes have been transmitted from cultures to cultures through agents of socialization. The reinforcement of these stereotypes has been internalized by both genders. However, these stereotypes has continuously portrayed a negative aspect of the female gender subjecting them to the dominance of men and reinforcing traditional views of the place and value of women in Nigerian society. The traditional Nigerian society enjoys such portrayals and provides the largest bulk of the content that fuels the stereotypes of women in Nollywood films. These films are becoming the template for Nollywood directors and producers. Therefore, this paper examines the repositioning of the narratives about gender stereotypes in Nollywood films especially as it relates to the negative portrayal of the female gender. Rather than focusing on the existent problem, this paper is an attempt to investigate how the Auteurs and Nego-feminism theory could be explored to assist female Auteurs/Producers at rewriting the narrative and perception of the film audience about of the negative portrayal of women in Nollywood films.